Improving Physical Properties of Nano Layered ITO Thin Films by using a Novel Oil Thermal Annealing - Hegde, Gurumurthy; Mehdi, Qasim; Jinan B., Al-Dabbagh; Ahmed, Naser Mahmoud; Mohamad Ashry, Jusoh (Landesmuseum Kärnten, 2014)
Indium tin oxide (ITO) thin film were deposited on glass substrates by RF sputtering technique, followed by two treatment techniques which are Oil thermal annealing (OTA) and Argon Gas. Atomic Force Microscopy (AFM) and X-ray diffraction were used to analysis the surface morphology and structure of ITO thin film. The structural, electrical and optical properties data for ITO films with thickness 150 nm obtained. After deposition, the samples have been annealed at 250 ºC by using oil and Argon gas. The optical properties after annealing by using a spectrophotometer show a high transparency between 81% and 95% in the visible spectrum. In addition, the sheet resistance of ITO film 9.65 k Ω / □ was significantly improved to 65 Ω / □ annealing time by using the OTA technique in comparison with 2.37 k Ω / □ under Argon gas at 10 minutes.